L’arrivée des premiers fers dans l’Occident atlantique - Raquel Vilaça (Mélanges de la Casa de Velázquez, 2013)
The author reviews the problematic issues raised by the introduction of the first iron artefacts in the context of social dynamics in the late 2nd and early 1st millennia BCE —i.e. at the end of the regional bronze age. Iron artefacts are characterised in terms of types, chronology and context —living spaces, rubbish pits, ritual deposits— on the basis of radio-carbon dating of samples taken as part of an investigation of archaeological contexts in several habitats in central Portugal. The incorporation of iron into the local material culture took place at an early date; and it was accompanied by other «Mediterranean traces», such as new materials or new techniques. The research also examines the reasons for adopting these early iron artefacts —practical advantages over bronze or simply prestige items— and sustains the view that the introduction of the new metal did not produce any profound overall changes in local communities at the close of the Bronze Age.